STRATEGI KOMUNIKASI PIMPINAN DALAM MENINGKATKAN KINERJA PEGAWAI DI DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA LUBUKLINGGAU - Tamri Tamri (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to (1) determine the leadership communication strategy in improving the performance of the employees of the Education and Culture Office of Lubuklinggau City. (2) determine the effectiveness of leadership communication on employee performance. (3) evaluate the performance of employees who are influenced by leadership communication. The research method used is a qualitative research data collection techniques used by using: interviews, observation, documentation. The data analysis technique that the researcher uses is descriptive qualitative analysis, namely data analysis in the form of words, pictures and not numbers. The results showed that the communication strategy carried out by the leader to subordinates, namely by means of dialogue, so that there was effective communication between leaders and subordinates, the leadership carried out effective communication with subordinates, both verbally and non-verbally, with effective communication there would be a dialogue between leadership and subordinates, so that both parties can understand and understand what is being discussed about communication between leaders and subordinates, there will be a harmonious dialogue, so that the leadership's orders to subordinates can be carried out properly.